The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1037/adb0000483
|View full text |Cite
|
Sign up to set email alerts
|

A systematic scoping review of research on Black participants in the National Drug Abuse Treatment Clinical Trials Network.

Abstract: Black individuals experience a disproportionate burden of substance-related disabilities and premature death relative to other racial/ethnic groups, highlighting the need for additional research. The National Drug Abuse Treatment Clinical Trials Network (CTN), a research platform for multisite behavioral, pharmacological, and integrated trials designed to evaluate the effectiveness of substance use treatments in community settings with diversified patient populations, provides a wealth of research knowledge on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 110 publications
(149 reference statements)
0
18
0
Order By: Relevance
“…34 Differential treatment retention is also evident among Black people receiving treatment for opioid, alcohol, stimulant, and cannabis use disorders. 35,36 Reasons for lower engagement and retention of Black individuals in SUD treatment are poorly studied, but likely due to less social, financial, and environmental supports, a lack of culturally-informed and responsive treatment, mistrust in the healthcare system, and unequal enforcement of treatment rules and requirements. 7,35,36 We would be remiss if we did not also address racial disparities in harm reduction and other services for persons who use drugs.…”
Section: Substance Use Treatment and Harm Reduction Services: Racial mentioning
confidence: 99%
See 1 more Smart Citation
“…34 Differential treatment retention is also evident among Black people receiving treatment for opioid, alcohol, stimulant, and cannabis use disorders. 35,36 Reasons for lower engagement and retention of Black individuals in SUD treatment are poorly studied, but likely due to less social, financial, and environmental supports, a lack of culturally-informed and responsive treatment, mistrust in the healthcare system, and unequal enforcement of treatment rules and requirements. 7,35,36 We would be remiss if we did not also address racial disparities in harm reduction and other services for persons who use drugs.…”
Section: Substance Use Treatment and Harm Reduction Services: Racial mentioning
confidence: 99%
“…35,36 Reasons for lower engagement and retention of Black individuals in SUD treatment are poorly studied, but likely due to less social, financial, and environmental supports, a lack of culturally-informed and responsive treatment, mistrust in the healthcare system, and unequal enforcement of treatment rules and requirements. 7,35,36 We would be remiss if we did not also address racial disparities in harm reduction and other services for persons who use drugs. Harm reduction refers to pragmatic interventions aimed at minimizing the negative effects of unhealthy behaviors without a prerequisite that the behavior(s) cease.…”
Section: Substance Use Treatment and Harm Reduction Services: Racial mentioning
confidence: 99%
“…Recent scoping reviews of CTN research involving both Blacks [3] and Hispanics [9] revealed that measurement equivalence cannot be assumed across substance using racial/ethnic groups. Measurement equivalence refers to the extent to which a measure assesses the equivalent underlying psychological construct in a group other than the group in which the measure was standardized.…”
Section: Assess For Measurement Equivalencementioning
confidence: 99%
“…These papers suggest that community engagement and the formation of academic/community research partnerships are both effective recruitment strategies [12,27,28]. Two recent scoping reviews of CTN research involving both Blacks [3] and Hispanics [9] revealed that measurement equivalence cannot be assumed across substance using racial/ethnic groups in CTN research. Moreover, several secondary analyses have revealed racial/ethnic differences in outcomes [3,[29][30][31][32][33].…”
Section: Infuse Decision-making With Racial/ethnic Expertisementioning
confidence: 99%
See 1 more Smart Citation